C3AR1 as a target for preeclampsia: from bioinformatics and network pharmacology to experimental validation - Yongfeng Hu; Shaoqiang Li; Yunhui Hong; Dongxian Peng (BMC Pregnancy and Childbirth)
Abstract Background Preeclampsia, characterized by hypertension and proteinuria during pregnancy, poses significant risks to both mother and fetus. The complement system’s aberrant activation, notably the C3AR1, is important to the pathogenesis of preeclampsia, although the precise mechanisms are not fully understood. Materials and methods Utilizing the Comparative Toxicogenomics Database (CTD) and Molecular Signatures Database (MSigDB), we identified complement system targets associated with preeclampsia and environmental pollutants. Expression validation was conducted through the Gene Expression Omnibus (GEO) database. Molecular docking predicted interactions between BPA, PFOS, and C3AR1. Immunohistochemical staining of 80 placental tissues (40 early-onset preeclampsia and 40 healthy controls) confirmed C3AR1 expression and its clinical correlation. Integrated bioinformatics analyses revealed C3AR1’s role in preeclampsia’s molecular mechanisms. Functional verification was assessed by knocking down C3AR1 in HTR-8/Svneo cells, including cell proliferation, invasion, and apoptosis. Results Network pharmacology established connections between pollutants and preeclampsia, with C3AR1 as a key target. Molecular docking confirmed BPA and PFOS binding to C3AR1. Reduced C3AR1 in preeclamptic placentas correlated with maternal blood pressure, and showed high diagnostic potential (AUC = 0.95). C3AR1’s involvement in preeclampsia was linked to Jak-STAT, TGF-β, and HIF-1 pathways, and associated with NK cell and M1 macrophage activity. C3AR1 knockdown in HTR-8/Svneo cells decreased proliferation and invasion, and increased apoptosis. Conclusion C3AR1 expression is diminished in preeclampsia placental tissues, correlating with disease severity, suggesting its potential as a biomarker. It is crucial for cellular functions and inflammation, with future studies aiming to leverage this for novel preeclampsia treatments. Clinical trial Not applicable.